Photocatalytic CO2 reduction to syngas using nickel phosphide-loaded CdS under visible light irradiation - Yadav, Poonam; Kumar, Santosh; Velankanni, Nandhakumar; Kuehne, Thomas D.; Gosavi, Suresh; Raghupathy, Ramya Kormath Madam; Bhosale, Reshma; Held, Georg; Shelke, Manjusha; Ogale, Satishchandra (Journal of Physics-Energy, 2024)
Photocatalytic CO2 reduction is a sustainable pathway to produce syngas (H-2 + CO), which is a key feedstock for the production of several important liquid fuels on the industrial scale. However, achieving an appropriate tunable ratio of H-2:CO in syngas for commercial purposes is a challenging task. In this work, we present a low-cost and non-noble metal, phosphide-based co-catalyst-Ni2P-loaded cadmium sulfide (CdS) photocatalyst system, for photocatalytic CO2 reduction. As a co-catalyst, Ni2P fosters an efficient charge separation of photoexcited charges generated in the CdS production of syngas. In total, 3 wt.% Ni2P/CdS exhibited exceptional performance of 50.6 mu mol g(-1) h(-1) in the CO evolution rate and 115 mu mol g(-1) h(-1) in the H-2 evolution rate, with a syngas composition varying from 2 to 4 in the H-2:CO ratio. Furthermore, first-principles density functional theory calculations were performed to study the surface energetics of the catalyst system and the results are found to be consistent with our experimental findings. Indeed, they establish that the composite favors CO2 photoreduction into syngas more efficiently than pure surfaces.
Keywords: CdS; CO2 reduction; Photocatalysis; Syngas; transition metal phosphides